Durabilitas Campuran AC-BC dengan Menggunakan Batu Gunung Bou Buya Kabupaten Poso - Darma Sapa'; Alpius; Charles Kamba (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
Durability is a property that must be possessed by an asphalt mixture so that the mixture can withstand the influence of water. Apart from being caused by a high water content, this is also influenced by the quality of the material used in the pavement mixture. The purpose of the study was to determine the durability value of the AC-BC mixture with the use of Bou Buya mountain rock. To determine the effect of immersion time which varies 0.5; 12; 24; 36; 48; and 60 hours with a standard temperature of 60 OC. The test method is based on the specifications of Bina Marga Division 6 of 2018. The purpose of this research is to obtain the results of Stability and Flow which are used to obtain the Durability value. The average durability value for each immersion is 12; 24; 36; 48; and 60 hours is 97.64%-89.22%. The durability value at 12 hours to 48 hours immersion meets the specifications but at 60 hours immersion does not meet the specifications, namely at least 90%. The effect on the immersion time varied 0,5; 12; 24; 36; 48; and 60 hours with a standard temperature of 60°C, it can be concluded that if the mixture is soaked for a long time, the durability value (durability) will be smaller. This is due to the large number of pores and cavities filled with water, so the mixture is not impermeable to water or easily damaged.